The value of telemonitoring and ICT-guided disease management in heart failure: Results from the IN TOUCH study. Issue 1 (January 2016) - Kraai, Imke; de Vries, Arjen; Vermeulen, Karin; van Deursen, Vincent; van der Wal, Martje; de Jong, Richard; van Dijk, René; Jaarsma, Tiny; Hillege, Hans; Lesman, Ivonne
Highlights: A multicenter randomized controlled trial to test the effects of an ICT- guided-DMS combined with telemonitoring in HF-patients (IN TOUCH trial). The intervention did not affect the primary endpoint of mortality, HF- readmissions and quality of life. Use of telemonitoring is safe and can reduce HF-related visits to the HF outpatient clinic keeping HF-care accessible. The adherence of patients using telemonitoring was very high indicating that the devices used in combination with daily measurements were well accepted by patients. Abstract: Aim: It is still unclear whether telemonitoring reduces hospitalization and mortality in heart failure (HF) patients and whether adding an Information and Computing Technology-guided-disease-management-system (ICT-guided-DMS) improves clinical and patient reported outcomes or reduces healthcare costs. Methods: A multicenter randomized controlled trial was performed testing the effects of INnovative ICT-guided-DMS combined with Telemonitoring in OUtpatient clinics for Chronic HF patients (IN TOUCH) with in total 179 patients (mean age 69 years; 72% male; 77% in New York Heart Association Classification (NYHA) III–IV; mean left ventricular ejection fraction was 28%). Patients were randomized to ICT-guided-DMS or to ICT-guided-DMS + telemonitoring with a follow-up of nine months. The composite endpoint included mortality, HF-readmission and change in health-related quality of life (HR-QoL). Results: In total 177 patients were eligible for analyses. The mean score of the primary composite endpoint was −0.63 in ICT-guided-DMS vs. −0.73 in ICT-guided-DMS + telemonitoring (mean difference 0.1, 95% CI: −0.67 +0.82, p = 0.39). All-cause mortality in ICT-guided-DMS was 12% versus 15% in ICT-guided-DMS + telemonitoring ( p = 0.27); HF-readmission 28% vs. 27% p = 0.87; all-cause readmission was 49% vs. 51% ( p = 0.78). HR-QoL improved in most patients and was equal in both groups. Incremental costs were €1360 in favor of ICT-guided-DMS. ICT-guided-DMS + telemonitoring had significantly fewer HF-outpatient-clinic visits ( p < 0.01). Conclusion: ICT-guided-DMS + telemonitoring for the management of HF patients did not affect the primary and secondary endpoints. However, we did find a reduction in visits to the HF-outpatient clinic in this group suggesting that telemonitoring might be safe to use in reorganizing HF-care with relatively low costs.